MOVIE RECOMMENDATION SYSTEM USING JAVASCRIPT (International Journal of Food and Nutritional Sciences, 2024)
Movie Recommendation System usually suggest what movies a user will like based on the attributes present in previously liked movies. These movie recommendation system helps to personalize a platform and helps the users to find something that they like based on their interests. In this paper, the recommendation system has been built on the type of genres that the user might prefer to watch. The traditional methods of movie recommendation consumes a lot of time for searching the interested movies. So, we proposed a system that produces the top 30 similar movies to the user based on genre given by the user. This project is based on python and similarity algorithms. We calculated the similarity scores between the movies in the dataset using cosine similarity algorithm. The system displays the top similar movies when a user gives a movie title. And this Project also organizes the information about movies in CSV file